Local Impacts of a Global Commodity: Small Tea Growers in a Northern District of Bangladesh - Mahmud, Asif (South Asian Journal of Social Sciences and Humanities, 2023)
This research explores the Small Tea Plantations (STP) in Romjanpara and Radhanagar villages of Atwari Subdistrict under the northernmost district of Bangladesh, Panchagarh and its impact on the local farmers. More specifically, how STP was integrated in the local farming, the socioeconomic conditions of the small tea growers and the problems they face in the trading of tea leaves. The northernmost part of Bangladesh was economically insolvent before the advent of STP. Now the economic condition is growing and more lands are coming under STP. But behind this scene, there are stories of class formation and exploitation of the small tea growers. The first-hand data is collected using Case Study, KII, FGD, Semi-structured Interview, and observation. Adopting Political economy of agrarian change as theoretical framework and based on qualitative interviews, this research provides an analysis of the socioeconomic conditions and problems that the small tea growers face. The findings show that the factories create and often perpetuate these problems and thus reproduce the existing socioeconomic differences.